GluN2B/CaMKII mediates CFA-induced hyperalgesia via HDAC4-modified spinal COX2 transcription. (June 2018) - Lai, Cheng-Yuan; Hsieh, Ming-Chun; Ho, Yu-Cheng; Chen, Gin-Den; Chou, Dylan; Ruan, Ting; Lee, An-Sheng; Wang, Hsueh-Hsiao; Chau, Yat-Pang; Peng, Hsien-Yu; Lai, Cheng-Hung
Abstract: Histone deacetylase 4 (HDAC4), which actively shuttles between the nucleus and cytoplasm, is an attractive candidate for a repressor mechanism in epigenetic modification. However, the potential role of HDAC4-dependent epigenetics in the neural plasticity underlying the development of inflammatory pain has not been well established. By injecting complete Freund's adjuvant (CFA) into the hind-paw of Sprague-Dawley rats (200–250 g), we found animals displayed behavioral hyperalgesia was accompanied with HDAC4 phosphorylation and cytoplasmic redistribution in the dorsal horn neurons. Cytoplasmic HDAC4 retention led to its uncoupling with the COX2 promoter, hence prompting spinal COX2 transcription and expression in the dorsal horn. Moreover, the GluN2B-bearing N-methyl-d -aspartate receptor (GluN2B-NMDAR)/calmodulin-dependent protein kinase II (CaMKII) acted as an upstream cascade to facilitate HDAC4 phosphorylation/redistribution-associated spinal COX2 expression after inflammatory insults. The results of this pilot study demonstrated that the development and/or maintenance of inflammatory pain involved the spinal HDAC4-dependent epigenetic mechanisms. Our findings open up a new avenue for the development of a novel medical strategy for the relief of inflammatory pain. Highlights: Spinal HDAC4 phosphorylation and cytoplasmic retention mediate CFA-provoked behavioral hyperalgesia. Spinal pGluN2B-NMDAR/pCaMKII cascade prompts HDAC4 phosphorylation/redistribution caused by CFA. Spinal pGluN2B/pCaMKII-dependent HDAC4 trafficking regulates COX2 transcription to mediate CFA-induced hyperalgesia.